2018
DOI: 10.1186/s13024-018-0250-z
|View full text |Cite
|
Sign up to set email alerts
|

Loss of XBP1 accelerates age-related decline in retinal function and neurodegeneration

Abstract: BackgroundAging is the strongest risk factor for neurodegenerative diseases and extended age results in neuronal degeneration and functional decline in the visual system. Among many contributing factors to age-related deterioration of neurons is an insufficient activation of the Unfolded Protein Response (UPR) in the endoplasmic reticulum (ER) in response to cellular stress. X-box binding protein 1 (XBP1) is a major component of the UPR and is essential for maintaining protein homeostasis and reducing cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 28 publications
2
45
0
2
Order By: Relevance
“…Mouse eye cryosections were prepared for immunohistochemistry as described previously (McLaughlin et al, 2018 ). The primary antibodies used were: Ribeye (Synaptic Systems 192003, 1:800); PKCα (Santa Cruz sc-8393, 1:400); Pax6 (DSHB Pax6-s, 1:25); and calretinin (Millipore Mab1658, 1:800).…”
Section: Methodsmentioning
confidence: 99%
“…Mouse eye cryosections were prepared for immunohistochemistry as described previously (McLaughlin et al, 2018 ). The primary antibodies used were: Ribeye (Synaptic Systems 192003, 1:800); PKCα (Santa Cruz sc-8393, 1:400); Pax6 (DSHB Pax6-s, 1:25); and calretinin (Millipore Mab1658, 1:800).…”
Section: Methodsmentioning
confidence: 99%
“…XBP1s is an important gene that turns on transcription of a subset of ER chaperones genes in response to stress. Previous studies have reported a pivotal role of XBP1 in the development of several diseases such as Alzheimer's Disease [43], diabetic retinopathy [44], neurodegeneration [45], insulin resistance [46], and obesity [47]. Sha et al [48] demonstrated that XBP1s improves glucose tolerance and insulin sensitivity in both lean and obese (ob/ob) mice by promoting adiponectin multimerization.…”
Section: Discussionmentioning
confidence: 99%
“…The ER does not need to be physically malformed to contribute to neurological disease, as ER stress has been linked to several neurodegenerative conditions (Hetz and Mollereau, 2014;Plate and Wiseman, 2017;Martínez et al, 2018;McLaughlin et al, 2018;Morris et al, 2018). ER stress occurs when the amount of unfolded proteins in the ER reaches an unmanageable level, triggering the unfolded protein response (UPR) (Martínez et al, 2018).…”
Section: Protein Synthesis Linked To Neurological Diseasementioning
confidence: 99%